PENGARUH AIDA (ATTENTION, INTEREST, DESIRE, ACTION) TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK BASUREK AL-SUFI DI KOTA BENGKULU - Ade Heriansya; Eti Arini (UM. Bengkulu, 2023)
The purpose of this study is to determine the effect of AIDA (Attention, Interest, Desire, Action) on purchasing decision Batik Basurek Al-SufiOf Bengkulu City and to find out which factors having the more dominant effect on the purchasing decision. The researcher used the questionnaire method to 102 respodents. The Population used were Batik Basurek Al-Suficonsumerof Bengkulu city. The sampling was the accindental sampling technique. Based on the results of multiple linear regression, the form of regression equation isY =0.869 + -0.068 () + 0.255 () + 0.893 (X3) + 0.551 (X4).The results of the research and the hypothesis show that the Attentionshows the value of >(-0.694< 1.988)and (sig = 0,489> 0,050),Interestshows the value of tcount>(2.498>1.988)and (sig = 0,014< 0,050), Desire shows the value of tcount>(18.864>1.988) and (sig = 0,000 < 0,050),Actionshows the value of tcount>(5.046>1.988)and (sig = 0,000 < 0,050). Parsial eously Attention haven’t a significant effect on purchasing decision. Parsial eously Interest, Desire, Action have a significant effect on purchasing decision. SimultaneouslyAttention, Interest, Desire, Actionhave a significant effect on purchasing decision. It is better if the producers can continue to maintain and even improve their products so that the main objectives of marketing can be achieved. Keywords : AIDA (Attention, Interest, Desire, Action), Buying Decission.